Setting up of pediatric trauma care in India - R Sharma; V Vasudevan; S Gupta (Wolters Kluwer Medknow Publications, 2017)
Pediatric trauma is a significant cause of mortality and disability, being responsible for more deaths than all diseases combined. The burden of child injuries in India is not clearly known. Timely recognition and intervention starting from the scene ofinjury and continuing during transport to care to pediatric trauma centre has decreased mortality rate by 25%. Over the years, the number of trauma Centres have increased with adequately equipped units but still care remains inadequate at multiple levels. The essential components for improving pediatric trauma care system in India are - (1) Setting up protocols for triage, quality transfer of pediatric trauma patients, ensuring adequate supply of equipment, appropriate utilization of available resources, implementation of basic quality improvement programmes like medical audit and continuous evaluation of quality of care by trauma system administration. (2) Effective linkage of major trauma centers in cities to each other and to liaison strong referral system between these tertiary level urban set-ups with rural territories where even basic trauma care is lacking (3) Encouraging staff with more experience in trauma care to work in such hospitals and continuing educational courses on trauma care for medical and paramedical personnel. Pediatric trauma is by and large a preventable condition. Therefore, injury prevention shouldbe apriority.